2013
DOI: 10.1016/j.apmr.2013.03.009
|View full text |Cite
|
Sign up to set email alerts
|

Chemotherapy-Related Neuropathic Symptoms and Functional Impairment in Adult Survivors of Extracranial Solid Tumors of Childhood: Results From the St. Jude Lifetime Cohort Study

Abstract: Objective To ascertain prevalence of peripheral sensory and motor neuropathy; to evaluate impairments in relation to function. Design St. Jude Lifetime Cohort Study, a clinical follow-up study designed to evaluate adverse late effects in adult survivors of childhood cancer. Setting St. Jude Children’s Research Hospital (SJCRH). Participants Eligibility required treatment for an extracranial solid malignancy between 1962 and 2002, age ≥18 years, ≥10 years post-diagnosis, no history of cranial radiation. 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
82
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 92 publications
(85 citation statements)
references
References 33 publications
0
82
0
3
Order By: Relevance
“…The platinum agents are still one of the major families of chemotherapy used as standard of care in a wide variety of cancer scenarios. However, despite the abundant use of platinum-based chemotherapy, little is known about the mechanisms by which these drugs cause neuropathy or how to prevent or treat this debilitating toxicity (Ness et al, 2013). Furthermore, unlike a number of other major chemotherapy side effects (e.g., nausea, hair loss, bone marrow failure; Zafar et al, 2010), there are no standard, Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The platinum agents are still one of the major families of chemotherapy used as standard of care in a wide variety of cancer scenarios. However, despite the abundant use of platinum-based chemotherapy, little is known about the mechanisms by which these drugs cause neuropathy or how to prevent or treat this debilitating toxicity (Ness et al, 2013). Furthermore, unlike a number of other major chemotherapy side effects (e.g., nausea, hair loss, bone marrow failure; Zafar et al, 2010), there are no standard, Fig.…”
Section: Discussionmentioning
confidence: 99%
“…10 In terms of assessment methods, only active DF-ROM has been measured, although previous studies reported that passive DF-ROM, as well as strength of ankle dorsiflexors, is reduced as well. 8,9,12,14,19,20,27 In addition, there are 2 other important limitations. The assessors were not blinded.…”
Section: Limitationsmentioning
confidence: 96%
“…These limitations may cause functional impairments, such as reduced walking efficiency, a reported late effect in pediatric oncology. 8,19,20 In practice, our team has noticed the tendency to run on tiptoes and the inability to walk on heels in a mixed childhood cancer survivor cohort. Therefore, we hypothesize that limitations in ankle DF-ROM, gait, and walking efficiency may affect various types of childhood cancer.…”
mentioning
confidence: 96%
“…Vinca alkaloids trigger neuropathy in about 20% of cancer patients; typical symptoms include lower limb weakness, sensory impairment, altered gait, and diminished reflexes. Using electrophysical techniques, nerve changes are diagnosed as predominantly moderate to severe sensory or sensorimotor polyneuropathies (Ness et al., 2013). Mechanisms underlying neurotoxicity of vinca alkaloids remain unclear; however, available evidence suggests that genetic polymorphism of genes crucial for microtubule formation might play a role in developing neuropathy in cancer patients (Diouf et al., 2015).…”
Section: Vinca Alkaloidsmentioning
confidence: 99%